Contents of Pigments and Activity of Antioxidant Enzymes in Rice Plants Pre-Treated with Sodium Nitroprusside and Exposed to Clomazone - K.S. SILVA; L.A. TABALDI; L.V. ROSSATO; B.M. CAVICHIOLI; V.B. BASÍLIO; S.L.O. MACHADO (Planta Daninha, 2019)
ABSTRACT: The pre-treatment of rice seeds with sodium nitroprusside (SNP) was used to investigate the effect of exogenous nitric oxide on the pigment content and the activity of antioxidant enzymes during the inhibition of the 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway by the herbicide clomazone. The seeds were soaked in SNP solution (200 mM) for one and 10 hours and sprayed with clomazone, at post-seeding and at the needle-point, with 612 (experiment 1) and 1,224 g a.i. ha-1 (experiment 2). The control of both factors received distilled water. Carotenoids, chlorophylls a, b and total, superoxide dismutase (SOD), guaiacol peroxidase (POD) and the correlation between the variables were evaluated in the shoot of the plants. When compared to the control (no SNP), the imbibition for one hour increased carotenoid and total chlorophyll content by 24 and 54%, respectively, in experiment 1, where clomazone was applied in post-seeding. In the absence of the herbicide, the values were 37 and 59% higher. The SOD and POD activity, respectively, was increased by 48 and 51%, when the seeds were soaked for 10 hours and exposed to 612 g a.i. ha-1 of clomazone in post-seeding application. In a similar condition, in experiment 2, there were no changes in enzyme activity. Seed pretreatment with SNP increases the carotenoid and chlorophyll contents in rice plants, even with the inhibition of the MEP pathway by clomazone. The behavior of the SOD and POD activity indicates that other mechanisms besides the increase in the photosynthetic pigment contents are involved in the detoxification of the reactive oxygen species induced by the mode of action of clomazone.